Contributions of voluntary activation deficits to hand weakness after stroke. Issue 6 (17th August 2016) - Hoffmann, Gilles; Conrad, Megan O.; Qiu, Dan; Kamper, Derek G.
Abstract : Background: Hemiparetic stroke survivors often exhibit profound weakness in the digits of the paretic hand, but the relative contribution of potential biomechanical and neurological impairment mechanisms is not known. Establishing sources of impairment would help in guiding treatment. Objective: The present study sought to quantify the role of diminished capacity to voluntarily active finger flexor and extensor muscles as one possible neurological mechanism. Methods: Two groups of stroke survivors with "severe" ( N  = 9) or "moderate" ( N  = 9) hand impairment and one group of neurologically intact individuals ( N  = 9) participated. Subjects were asked to create isometric flexion force and extension force, respectively, with the tip of the middle finger. The maximum voluntary force (MVF) and the maximum stimulated force (MSF) produced by an applied train of electrical current pulses (MSF) were recorded for flexion and extension. Percent voluntary activation (PVA) was computed from MVF and MSF. Results: Significant deficits in both MVF and PVA were observed for stroke subjects compared to control subjects. For example, activation deficits were >80% for extensor digitorum communis (EDC) for the "severe" group. Maximum voluntary force and PVA deficits were greater for EDC than for flexor digitorum superficialis (FDS) for stroke subjects with severe impairment. Maximum voluntary force and PVA correlated significantly for stroke subjects but not for control subjects. Conclusions: Although extrinsic finger muscles could be successfully recruited electrically, voluntary excitation of these muscles was substantially limited in stroke survivors. Thus, finger weakness after stroke results predominantly from the inability to fully activate the muscle voluntarily.